Relation between the level of lymph node metastasis and survival in locally advanced head and neck squamous cell carcinoma. Issue 4 (10th November 2015) - Xing, Yan; Zhang, Jianjun; Lin, Heather; Gold, Kathryn A.; Sturgis, Erich M.; Garden, Adam S.; Lee, J. Jack; William, William N.
Abstract : BACKGROUND: The current head and neck squamous cell carcinoma (HNSCC) staging system may not capture the full prognostic implications of regional lymph node involvement. This study investigated the impact of the level of lymph node metastasis (LNM) on survival. METHODS: The Surveillance, Epidemiology, and End Results registry was queried for oral cavity (OC), oropharynx (OP), larynx (LAR), and hypopharynx (HP) HNSCC. A multivariate Cox proportional hazards model was used to evaluate whether the level of LNM was an independent prognostic factor. Site‐specific recursive‐partitioning analysis was performed to classify patients into different risk groups. RESULTS: In all, 14, 499 patients, including OC (n = 2463), OP (n = 8567), LAR (n = 2332), and HP patients (n = 1137), were analyzed. Both the American Joint Committee on Cancer (AJCC) N classification and the level of LNM showed significant effects on overall survival (OS) in patients with OC, OP, or LAR HNSCC but not in patients with HP HNSCC. In patients with N2 disease, the AJCC subclassification (N2a, N2b, or N2c) was significantly associated with the OS of patients with OP and LAR HNSCC but not with the OS of patients with OC or HP HNSCC, whereas the level of LNM (primary, secondary, or tertiary) was significantly associated with the OS of patients with OC, OP, and LAR HNSCC but not HP HNSCC. With recursive‐partitioning analysis, a simple, primary site–specific prognostic tool integrating the AJCC T and N classifications and the level of LNM was designed, and it could be easily used by health care providers in clinic. CONCLUSIONS: The level of LNM is an independent prognostic factor for patients with locally advanced HNSCC and could add to the prognostic value of AJCC T and N classifications in patients with locally advanced HNSCC. Cancer 2016;122:534–545. © 2015 American Cancer Society . Abstract : The level of lymph node metastasis is an independent prognostic factor for patients with locally advanced head and neck squamous cell carcinoma. It could add prognostic value to the American Joint Committee on Cancer T and N classification for patients with locally advanced head and neck squamous cell carcinoma.